Implementation of Case Management in Improving Quality of Service in Islamic Hospital Purwokerto (Case Study Patient DM Type II) - Rini Indrian (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2018)
Quality service is a service based on Patient Center Care that requires integration and coordination of various care providers. Lack of communication, coordination and collaboration between caregivers and dissatisfaction of patients can affect the quality of service. To find out communication, collaboration, coordination and satisfaction of care givers and patient satisfaction by using Case Management implementation. This research is a qualitative research using Action Reaserch method. The tools used in the study used interviews. The results of the study before the implementation of Case Management 3 of 4 Case Managers said that (communication, coordination and collaboration) the care giver was still lacking, and was not satisfied in providing services, and 3 patient respondents said they were not satisfied with inpatient services. After the Case Management implementation, 5 of the 6 Case Managers said (communication, coordination and collaboration) had increased more than before, and were satisfied in providing services to patients in inpatient installations. While for respondents with patient satisfaction (case study of DM patients), 11 of 15 patients said they were satisfied, 4 patients said they were not satisfied with the service. The implementation of Case Management carried out in inpatient installations is able to improve the quality of service (communication, coordination, and collaboration) of the care givers and increase the satisfaction of officers in providing services to patients inpatients, and provide patient satisfaction while getting services in hospital inpatient installations islam purwokerto.